Cytokine profile of scrub typhus patients during the acute phase of illness - Afaf Shuaib; Asfia Sultan; Mohd Azam; Meher Rizvi; Fatima Khan; Haris M Khan; Mohd Shahid (Wolters Kluwer Medknow Publications, 2023)
Background: An early and effective immune response has a role in disease presentation and clearance of pathogen. Chemokine and cytokine responses in the immunopathogenesis of scrub typhus (ST) are the least explored aspect. This study aimed to analyze interleukin (IL)-2, IL-6, tumor necrosis factor-alpha (TNF-α), IL-10, transforming growth factor (TGF)-β, and human macrophage inflammatory protein-1 (HMIP-1) β cytokine levels in ST-positive patients during the acute phase of illness. Materials and Methods: A total of 112 ST-positive patients were included in the study with 30 healthy controls (HC). Diagnosis was confirmed by immunoglobulin M enzyme-linked immunosorbent assay (ELISA) and indirect immunofluorescence assay. The serum levels of cytokines were measured using the ELISA. Statistical analysis was performed with the IBM SPSS Statistics 20 and MedCalc 16.1 Software. Results: The mean level of IL-6, IL-10, TNF-α, and HMIP1-β (72 pg/ml, 86.7 pg/ml, 187.05 pg/ml, and 12.23 pg/ml vs. 7.30 pg. ml, 8.73 pg/ml, 56.62 pg/ml, and 6.94 pg/ml, respectively) was significantly raised among the ST patients compared to the control group (P < 0.001) However, the mean and median levels of IL-2 and TGF-β were not differed significantly between ST patients and HC (P = 0.0207 and 0.0386, respectively). The severity of the disease involved respiratory complications. Around 90.1% (101/112) of patients showed high levels of IL-6, whereas IL-10, TNF-α, and HMIP-1 β levels were raised in 97 (86.6%), 63 (56.2%), and 69 (61.6%) cases, respectively. There was a higher TNF-α level in severe cases with a few values up to 298.77 pg/ml. Conclusion: Proinflammatory cytokines and IL-10 were found to be increased in ST patients during the acute phase of infection. A proper balance of these cytokines is required for a better outcome. These findings suggest that the status of TNF-α levels in the acute phase may predict the severity of ST disease.